COMPARISON OF THE OUTCOMES OF PHACOEMULSIFICATION AND MANUAL SMALL-INCISION CATARACT SURGERY IN POSTERIOR POLAR CATARACT – A RETROSPECTIVE STUDY - Mandal, Govind Kumar; Choudhary, Jagdish; Roy, Pummy (Student's Journal of Health Research Africa, 2024)
Background Surgical challenges arise from posterior polar cataracts (PPC) due to their unique characteristics and fragility of the posterior capsule. These cases increase the risk of posterior capsular rupture (PCR), requiring careful surgical planning and technique selection. Phacoemulsification and MSICS are used, but their efficacy and safety in posterior polar cataracts (PPC) are still being studied. Objective: Compare intraoperative complications, visual outcomes, and postoperative recovery of phacoemulsification and MSICS in posterior polar cataract patients. Methods This 22-month retrospective analysis was done at Jawahar Lal Nehru Medical College and Hospital, Bhagalpur. The surgical approach divided 72 PPC patients into two groups: Group A (n=36) received phacoemulsification, while Group B received MSICS. Patient records were reviewed for demographics, intraoperative events (PCR and vitreous loss), BCVA, and postoperative sequelae. Results The study found that posterior capsular rupture was more common in the MSICS group (19.4%) compared to the phacoemulsification group (11.1%), but the difference was not significant (p>0.05). MSICS had 8.3% vitreous loss compared to 2.8% in phacoemulsification. Group A had 80.5% BCVA ≥6/12 at one month, while Group B had 77.7%. MSICS patients had slightly higher postoperative inflammation, but it subsided by the first follow-up. No dropped nucleus or endophthalmitis was reported. Conclusion Careful phacoemulsification and MSICS can yield positive visual outcomes in posterior polar cataract surgery. Despite its technological complexity, phacoemulsification may reduce posterior capsular issues. MSICS remains viable, especially in resource-constrained environments. For fewer complications and better results, surgery experience, technique adjustments, and postoperative awareness are essential.